Development of mobile billing application system for PAMDES water meter data logging - Umar Ali Ahmad; Ikbal Ramdani; Fath Muhammad Isham; Reza Rendian Septiawan; R Rogers Dwiputra Setiady; Angga Rusdinar; Ashri Dinimaharawati; Yusup Diva Pratama; Fauzi Sofyan; Rifdo Shah Alam (JURNAL INFOTEL, 2022)
Along with the growth of Sindangsari's population, the water requirement in this village has increased. So, the drinking water company (PAMDES) in this village must be able to manage the available water to meet the necessities of public life. Now, the water company is still collecting and recording water meters manually. It is very risky to consider the water condition in the village because an officer can make a human error while recording the water meter's value. When the water meter recorder is damaged, the officer estimates the water meter's value. An application is needed to manage bills and record water meters to avoid this in previous studies using the Internet of Things (IoT) or mobile applications that must be sent online to the server in real-time. This solution is not suitable for the internet condition in Indonesia, which is not evenly distributed to remote villages. This study proposes to use a mobile application that can store data on mobile devices. When the internet connection is unavailable, it can be sent later when it is available again. In this study, data obtained that the condition of the meter recorder from 672 customers, 37 water meters recorder is damaged. In addition, water meter data is also obtained for the following month's bill and data on average water usage of 10,661m3 per month. With these data, it is found that the minimum water requirement is 10,661 m3 per month. It is hoped that the application for billing management and recording of PAMDES water meters in Sindangsari village, Cikoneng sub-district, Ciamis district can help increase PAMDES management capacity.